Foreign investors and domestic company growth: Evidence from US venture capital investments in Sweden - Thomas Hellmann; Alexander Montag; Joacim Tåg (Research Institute of Industrial Economics (IFN), 2019)
Do foreign venture capitalists help the domestic economy, or hamper it by slowing down growth, potentially moving economic activity away? This paper addresses this long-standing policy question by examining the differential effects of US venture capital investments on the growth of Swedish start-up companies. It finds that US venture capital results in more employment, not less. These findings continue to hold after controlling for endogenous selection effects. US investments are also accompanied by increases in local employment and start-up rates. The paper also examines effect on wages, sales, earnings, foreign subsidiaries, subsequent funding rounds, and exits. Overall there is no evidence that US venture capital investments hamper the domestic growth of Swedish companies
Keywords: G24; J21; F16; F30; F65; F66; 330; Domestic; Employment; Foreign; International; Venture Capital